A Leader's Guide to Cybersecurity - Parenty, Thomas; Domet, Jack (Ascent Audio, 2019)
Companies are investing an unprecedented amount of money to keep their data and assets safe, yet cyberattacks are on the rise-and the problem is worsening. No amount of technology, resources, or policies will reverse this trend. Only sound governance, originating with the board, can turn the tide. Protection against cyberattacks can't be treated as a problem solely belonging to an IT or cybersecurity department. It needs to cast a wide and impenetrable net that covers everything an organization does-from its business operations, models, and strategies to its products and intellectual property. And boards are in the best position to oversee the needed changes to strategy and hold their companies accountable. Not surprisingly, many boards aren't prepared to assume this responsibility. In A Leader's Guide to Cybersecurity, Thomas Parenty and Jack Domet, who've spent over three decades in the field, present a timely, clear-eyed, and actionable framework that will empower senior executives and board members to become stewards of their companies' cybersecurity activities. Filled with tools, best practices, and strategies, A Leader's Guide to Cybersecurity will help boards navigate this seemingly daunting but extremely necessary transition.